Comparison of router testbeds: embedded system-based, software-based, and multiprotocol label switching (MPLS) - M. H. M. Nasir; N. A. M. Radzi; W. S. H. M. W. Ahmad; F. Abdullah; M. Z. Jamaludin (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
Multiprotocol Label Switching (MPLS) is a promising packet switching technology in the field of communication network, allowing router to forward the packets based on labels. However, off-the-shelves routers are made to be non-configurable, making it less suitable for academic research purposes. The aim of this paper is to explore the possibility of developing a configurable MPLS router by reviewing embedded system-based router, software-based router and commercial MPLS router itself. The architecture of the routers will be described in detail and their performances will be compared. From the analysis, we found that the development of reconfigurable MPLS router testbed is achievable by using embedded system-based hardware due to its freedom of reconfigurability.